2021
DOI: 10.7203/sjp.18.1.21627
|View full text |Cite
|
Sign up to set email alerts
|

Editorial

Abstract: Han pasado 8 años desde mi saludo y declaración de intenciones como editora, en el número 10(2) de la revista. Publicamos los correspondientes 8 volúmenes, cada uno con un numero de páginas comprendido entre 250 y 350, y un nuero de trabajos entre 20 y 27. Además, se publicaron 5 volúmenes extraordinarios. Además, durante el periodo se publicaron 5 volúmenes extraordinarios con las mismas exigencias de calidad que los ordinarios y reuniendo entre todos ellos 90 trabajos. Todo este gran volumen de obra impresa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The roominess increased in the Hybrid layout because of the LHD load ore from the production drift. The triangular configuration of the extraction drift decreased the span between the production and extraction drift; this is also observed in the ‘offset’ herringbone layout (Chacon 1980).…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The roominess increased in the Hybrid layout because of the LHD load ore from the production drift. The triangular configuration of the extraction drift decreased the span between the production and extraction drift; this is also observed in the ‘offset’ herringbone layout (Chacon 1980).…”
Section: Resultsmentioning
confidence: 74%
“…On the other hand, Table 4 shows the result of the comparison criteria (Chacon 1980). Here, it can be observed that the utilization of the area over the drawpoint increases in the Hybrid layout because of the location of the drawpoint that also decreases the layout distortion and anisotropy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations